CULTURE OF SPEECH AS AN INDICATOR OF THE LEVEL OF FORMATION OF NATIONAL SELF-CONSCIOUSNESS (Pedagogy of Higher and Secondary Education, 2010)
Realize attempt fixing relation between level forming culture of speech students and degree expressing their of ethic's identification in the article.